2012
DOI: 10.1021/cm3011327
|View full text |Cite
|
Sign up to set email alerts
|

Controlling The Activator Site To Tune Europium Valence in Oxyfluoride Phosphors

Abstract: A new Eu3+-activated oxyfluoride phosphor Ca12Al14O32F2:Eu3+ (CAOF:Eu3+) was synthesized by a solid state reaction. Commonly red line emission was detected in the range of 570–700 nm. To achieve the requirement of illumination, this study revealed a crystal chemistry approach to reduce Eu ions from 3+ to 2+ in the lattice. Replacing Al3+–F– by the appreciate dopant Si4+–O2– is adopted to enlarge the activator site that enables Eu3+ to be reduced. The crystallization of samples was examined by powder X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(92 citation statements)
references
References 61 publications
(87 reference statements)
0
92
0
Order By: Relevance
“…49 Thus, it can be concluded that the local environment and size of the replaced crystal-site (Ca 2+ in this system) play a dominant role in the reduction of Eu 3+ . 12,50 Through the crystal-site engineering approach, we introduced Si 4+ −Ca 2+ into the CaYAlO 4 host to replace Al 3+ −Y 3+ attempting to shrink the AlO 6 octahedrons, accompanied by the expansion of CaO 9 polyhedron, then fulfilling the conditions for the reduction of Eu 3+ , because Si 4+ has a smaller radius than Al 3+ and substitution of Y 3+ by Ca 2+ can achieve charge compensation in the whole structure. 11,12,51 As the XRD pattern shows in Supporting Information Figure S3, impurities began to appear when x exceeded 0.30; thus, we restricted the x value to a maximum of 0.30.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…49 Thus, it can be concluded that the local environment and size of the replaced crystal-site (Ca 2+ in this system) play a dominant role in the reduction of Eu 3+ . 12,50 Through the crystal-site engineering approach, we introduced Si 4+ −Ca 2+ into the CaYAlO 4 host to replace Al 3+ −Y 3+ attempting to shrink the AlO 6 octahedrons, accompanied by the expansion of CaO 9 polyhedron, then fulfilling the conditions for the reduction of Eu 3+ , because Si 4+ has a smaller radius than Al 3+ and substitution of Y 3+ by Ca 2+ can achieve charge compensation in the whole structure. 11,12,51 As the XRD pattern shows in Supporting Information Figure S3, impurities began to appear when x exceeded 0.30; thus, we restricted the x value to a maximum of 0.30.…”
Section: Resultsmentioning
confidence: 99%
“…12,50 Through the crystal-site engineering approach, we introduced Si 4+ −Ca 2+ into the CaYAlO 4 host to replace Al 3+ −Y 3+ attempting to shrink the AlO 6 octahedrons, accompanied by the expansion of CaO 9 polyhedron, then fulfilling the conditions for the reduction of Eu 3+ , because Si 4+ has a smaller radius than Al 3+ and substitution of Y 3+ by Ca 2+ can achieve charge compensation in the whole structure. 11,12,51 As the XRD pattern shows in Supporting Information Figure S3, impurities began to appear when x exceeded 0.30; thus, we restricted the x value to a maximum of 0.30. First, Rietveld refinement with GSAS program has been performed to reveal more details to clarify how substitution (Si 4+ −Ca 2+ for Al 3+ −Y 3+ ) affects the Ca 0.99+x Y 1−x Al 1−x Si x O 4 :Eu 0.01 (CYASO, x = 0−0.30) crystal structure and luminescence properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Now in this case v opt (O) = 3.2 and v uncorr (Eu) = 1.78 which implies the energy of the O 2p ? Eu 4f CT band as 42,600 cm À1 and it should be near 235 nm [25]. The presence of the CT band indicates the strong covalency between Eu 3+ and O 2À in the prepared phosphors [26].…”
Section: Uv-vis Measurementsmentioning
confidence: 99%